Neutron-irradiated antibody-functionalised carbon nanocapsules for targeted cancer radiotherapy. (June 2020) - Wang, Julie Tzu-Wen; Spinato, Cinzia; Klippstein, Rebecca; Costa, Pedro Miguel; Martincic, Markus; Pach, Elzbieta; Ruiz de Garibay, Aritz Perez; Ménard-Moyon, Cécilia; Feldman, Robert; Michel, Yves; Šefl, Martin; Kyriakou, Ioanna; et al.
Abstract: Radiotherapy is a cancer treatment utilising high doses of ionizing radiation to destroy cancer cells. Our team has pioneered neutron activation of 152 Sm, filled and sealed into single-walled (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), to create stable and high-dose radioactive carbon nanocapsules for cancer radiotherapy. In this work, MWCNTs filled with enriched 152 SmCl3 (Sm@MWCNTs) were sealed and irradiated, followed by surface functionalisation with an epidermal growth factor receptor (EGFR)-targeting antibody. Characterisation of functionalised Sm@MWCNTs was carried out using thermogravimetric analysis, gel electrophoresis and transmission electron microscopy. The organ biodistribution of the radioactive functionalised 153 Sm@MWCNTs and therapeutic efficacy were studied in an experimental melanoma lung metastatic tumour model in mice after intravenous injection. Quantitative biodistribution analyses showed high accumulation of 153 Sm@MWCNT-Ab in lung. Significant tumour growth reduction was induced by both treatments of 153 Sm@MWCNTs functionalised with or without the antibody after a single intravenous injection. Although EGFR targeting showed no improvement in therapeutic efficacy, reduced spleen toxicity and normal haematological profiles were obtained for both functionalised derivatives. The current study demonstrated the possibility of performing chemical functionalisation and antibody conjugation on radioactive nanocapsules post-irradiation for the preparation of targeted radiopharmaceuticals. Graphical abstract: Image 1